Comparison of Osteogenesis between Adipose-Derived Mesenchymal Stem Cells and Their Sheets on Poly-ε-Caprolactone/β-Tricalcium Phosphate Composite Scaffolds in Canine Bone Defects. (16th August 2016) - Kim, Yongsun; Lee, Seung Hoon; Kang, Byung-jae; Kim, Wan Hee; Yun, Hui-suk; Kweon, Oh-kyeong
Abstract : Multipotent mesenchymal stem cells (MSCs) and MSC sheets have effective potentials of bone regeneration. Composite polymer/ceramic scaffolds such as poly- ε -caprolactone (PCL)/β -tricalcium phosphate (β -TCP) are widely used to repair large bone defects. The present study investigated the in vitro osteogenic potential of canine adipose-derived MSCs (Ad-MSCs) and Ad-MSC sheets. Composite PCL/β -TCP scaffolds seeded with Ad-MSCs or wrapped with osteogenic Ad-MSC sheets (OCS) were also fabricated and their osteogenic potential was assessed following transplantation into critical-sized bone defects in dogs. The alkaline phosphatase (ALP) activity of osteogenic Ad-MSCs (O-MSCs) and OCS was significantly higher than that of undifferentiated Ad-MSCs (U-MSCs). The ALP, runt-related transcription factor 2, osteopontin, and bone morphogenetic protein 7  mRNA levels were upregulated in O-MSCs and OCS as compared to U-MSCs. In a segmental bone defect, the amount of newly formed bone was greater in PCL/β -TCP/OCS and PCL/β -TCP/O-MSCs/OCS than in the other groups. The OCS exhibit strong osteogenic capacity, and OCS combined with a PCL/β -TCP composite scaffold stimulated new bone formation in a critical-sized bone defect. These results suggest that the PCL/β -TCP/OCS composite has potential clinical applications in bone regeneration and can be used as an alternative treatment modality in bone tissue engineering.